The seismicity of the British Isles - R. M. W. Musson (Annals of Geophysics, 1996)
A new and homogeneous catalogue of earthquakes in the British Isles has been produced, including events of magnitude 4 ML and greater to 1700 and events of 3 ML and greater thereafter. The distribution of seismicity is uneven, with some areas (e.g Ireland) almost aseismic. Magnitude/frequency analysis shows that a double-tl.uncated exponential distribution gives a better fit than a classic Gutenberg-Richter linear fit. Thecacnlated b value for the linear part of the exponential distribution is 0.94 with a maximum magnitude of 6.2 ML.